The use of an alternating magnetic field in the resorption of postoperative joint effusion following anterior cruciate ligament reconstruction: A randomized double-blind controlled trial. Issue 27 (9th July 2021) - Ogrodzka-Ciechanowicz, Katarzyna; Głąb, Grzegorz; Ciszek-Radwan, Elżbieta; Ślusarski, Jakub; Gądek, Artur
Abstract: Context: There are no scientific reports unambiguously describing the efficacy of alternating magnetic field therapy in patients after anterior cruciate ligament (ACL) reconstruction in the early postoperative period. Objective: This study aims to evaluate the efficacy of using an alternating magnetic field in the resorption of postoperative joint effusion in patients after ACL reconstruction. Study design: A randomized, double-blind placebo-controlled study. Setting: Inpatients. Participants: Forty patients were enrolled in the trial. However, the final study group consisted of 38 patients (28 men and 10 women) after ACL reconstruction who were randomly divided into an experimental group (19 patients) and a control group (19 patients). Intervention: Each group received magnetic field therapy in the postoperative period, but only 1 apparatus emitted a magnetic field (the experimental group). Patients used the apparatus every day for 30 minutes for the next 11 days. The parameters in both devices were the same—3 mT and 10 Hz. Main outcome measures: The measurement of the knee circumference and range of motion were made. The knee circumference measurement was performed before magnetic field therapy began and for 11 days after magnetic field treatment. The active knee range of motion was evaluated before and after magnetic field therapy was completed. Results: There were no statistically significant differences between the groups in the reduction of post-operative joint effusion or knee joint function. Conclusion: In patients after ACL reconstruction, in whom an alternating magnetic field was used to treat postoperative joint effusion, there were no beneficial effects on the analyzed variables compared to the control group.